SAVI Approach Paper 11: Managing and Staffing an Adaptive Citizen Engagement Programme - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme putting learning and adaptation at the centre of all decision-making. In relation to management and staffing SAVI has established the following approaches to facilitate this: – An adaptive approach to programme management: Full time strategic technical leadership, that works closely with and complements...

Adaptive Management in Practice: a case study on the Prospects program - Maclay, Chris (Prospects practice paper, 1, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Adaptation in practice: lessons from teenage pregnancy programmes in Sierra Leone - Castillejo, Clare; Buell, Stephanie (ODI, 2020)
A discussion of initial learning emerging from the SLRC ’Adaptive approaches to reducing teenage pregnancy in Sierra Leone’ action research project.

Wildlife laws monitoring as an adaptive management tool in protected area management in Ghana: a case of Kakum Conservation Area - Wiafe, Edward Debrah (SpringerPlus, 2016)
INTRODUCTION: The wildlife laws of Ghana alienated the rural communities from forests and material well-being depended upon for their livelihood and this manifests itself in the progressive conflict between the park patrol staff and poachers from the fringes of the protected areas. CASE DESCRIPTION: The main aim of this study was to determine the impact of quantification of patrol efforts on indicators of illegal hunting activities that occur in rainforest protected areas, as a result of monitoring patrol operations and modifying the original plan. The specific objectives were to determine the optimal patrol efforts necessary to reduce illegal wildlife use to minimal; and the influence of the rainfall and seasonal activities on illegal wildlife use. DISCUSSION AND EVALUATION: The results indicated that as the patrol efforts increased the encounter with illegal wildlife use also increased until a certain point that the encounter rates started decreasing. Neither rainfall nor seasonal activities influenced the illegal activities and the patrol efforts. The protection staff of rainforest protected areas would work effectively to bring down illegal wildlife off-take to the barest minimum if monitored, quantified and provide feed-back. CONCLUSIONS: Illegal wildlife off-take can also be reduced by the protection staff if the original plans are made flexible to be adjusted. Recommendations for further studies have been made.

Study on application of Adaptive Management (AM) in Education Out Loud (EOL) project implementation in the Horn, Eastern adn Southern Africa (HESA) - ANHRE (Oxfam, 2022)
This study mainly aimed to look at adaptive management in the program cycle (throughout Program Cycle processes, including strategy, project, and activity design and implementation) and to look at the Enabling Conditions: how an organization’s culture, business processes, and resource allocation support adaptive management. It explores elements of adaptive management that correspond to the objectives of the study as follows: 1) Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology. 2) Examine how adaptive management has been applied in EOL project implementation thus far. 3) Explore ways in which an adaptive management approach can be used as a source of learning during project implementation. 4) Propose ways in which the application of adaptive management can be improved in EOL project implementation. Objective 1: Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology: The researchers asessed whether the EOL program, GMU, and HESA RMU have a culture of openness, continuous learning, reflection, and improvement. This assessment looked at actual practices and perceptions of field-based staff and project officers. In addition, they looked at processes to assess knowledge management and decision-making process – the ability to distill, share and disseminate knowledge and the awareness among grantees/ employees of the decision-making process. Summary of findings: Understanding of adaptive management as a programming approach among the selected sample of grantees was linked to continuous learning, the ability to adjust implementation and inform decision making to reach the intended objectives based on analysis and assessment of the context and flexibility in management. RMU HESA was perceived to have a culture of openness where grantees feel comfortable sharing their opinion and ideas and is perceived to be receptive to proposed changes to projects and encourage grantees to provide feedback. The HESA RMU-Oxfam Denmark is also seen as an agency that is very “flexible“. Recommendations: Enhance Capacity building on adaptive management tools, particularly for finance and admin teams with a focus on pro-active adaptive management which scans the horizon for opportunities and risks, and it adapts to take advantage of them. It explicitly plans for experimentation and regular upgrading of the strategies; it considers learning and the reduction of uncertainty and imperfect knowledge as one of the key objectives of the management effort. Objective 2: Examine how adaptive management has been applied in EOL project implementation thus far Methodology: Two elements were assessed : Collaboration and how internal and external collaboration of grantees and grant agent, assessing the ability to collaborate with other departments within the entity, the ability to collaborate with learning partners, other grantees, to what extent they consult their stakeholders and their ability to build coalitions. In addition, researchers looked at Adaptation and the best practices and lessons learned in adopting change in the design, implementation, budgeting or monitoring of EOL programs and the process followed to adapt the desired change. Summary of findings: Adaptive management practices are seen to be adapting to context changes, constant learning, and flexibility. The management and coordination of EOL program is deemed to be collaborative, adaptive, and understanding of the emerging needs of EOL Program implementation. There is a simple process in place for grantees to make changes to the program implementation. Most grantees do take the time to pause and reflect on what is going well and what could be improved and to share the knowledge gained with their coalition members and regional coalitions. HESA RMU was found to be encouraging learning practices through organizing periodic online and offline regional learning and reflection workshops. Compared to other donors, the majority of grantees believe that EOL provided the highest level of flexibility and ability to adapt which is seen to be a necessity for advocacy work. However, it is important to enforce structure to tighten the feedback loop between data and action: adaptive management aims for double learning more than just correcting deviations in planned versus actual. Recommendations: Introducing outcome harvesting tool as one of the mechanisms to capture outcomes, institutionalization of adaptive management further by developing context analysis tools/ regular reviews of TOC. Further use of Scenario planning as a tool to map and plan different scenarios on how change may happen, and to examine the program’s role in making future events happen, enforcing structure to tighten the feedback loop between data and action. In addition to the introduction of quarterly planning cycles where data and information gathered in the previous quarter can be used to inform the next planning cycle and update the TOC, project design and activity implementation strategies. Objective 3: To explore ways in which an adaptive management approach can be used as a source of learning during project implementation Methodology: The team assessed the grantees’ ability to use evidence to build their pathways for change, their ability to use learning to inform decision making, the frequency and habit of reviewing their theory of change, the risks and opportunities through scenario planning, how they assess the efficiency of their data collection tools and monitoring and evaluation data quality, on whether they have a mechanism to monitor unintended outcomes (outcome harvesting) and reflect. Summary of findings: This study revealed that there is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program has adopted Re-active Adaptive Management that relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. Recommendations: Encouraging further engagement on knowledge sharing hubs and investing in knowledge transfer on adaptive management and learning to other partners in targeted countries (EOL to become an influencer in this field), encouraging further engagement from learning partners to provide mentorship and support during implementation and continuous learning on adaptive management tools. RISP and GISP could be further engaged in the monitoring process. Based on the stated objective, what was assessed and findings, it would also be interesting to enable grantees distill learnings from AM practices and applying that knowledge to improve project implementation. This means AM will be expected to go beyond changing implementation strategies and budgets and document learnings from such changes and apply them to improve the remaining part of the project. Objective 4: Propose ways in which the application of adaptive management can be improved in EOL project implementation Summary of findings: Grantees were able to articulate well their understanding of adaptive management but were less able to provide concrete examples of how adaptive management is implemented in practice. There is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. However, it is important to enforce structure to tighten the feedback loop between data and action and to institutionalize practicing adaptive management. Recommendations: A roadmap that looks at reviewing seven steps for improving adaptive management is recommended as a systematic tool to introduce improvement. This roadmap is useful in a multi-organizational, multi-country set-up where efficient design is needed to align top-down structuring and requirements with bottom-up diversity and divergence. This roadmap of seven steps is introduced by HIVOS. These 7 steps can come in a different order and it depends on the user to assess which of the seven steps needs to be undertaken. 1. Annual Review results/ outcome statements: using outcome harvesting to continuously monitor intended/ unintended outcomes (whether positive or negative or within the sphere of control (outputs) or within the sphere of influence (outcomes). 2. Learning questions: Learning from the monitoring data; Learning about the critical Make-or-Break assumptions in the Theory of Change; and Developing learning topics/ questions and learning agenda at each level 3. Changes in context: Identifying possible trends and signs about emerging shifts in the environment, followed by analyzing and collective sense-making of possible implications for the Theory of Change (is there a need to revise intervention strategies, desired outcomes, pathways, assumptions? 4. Theory of change: Reviewing the theory of change was not seen as a frequently recommended practice. Constant validation of pathways to change and evidence in the TOC is important. 5. Capacity assessment and development: What capacities are available amongst the alliance members and partner organizations in relation to the (revised) Theory of Change; What would be Capacity Development needs in view of the capacity assessment results? 6. Strategies and interventions: With the outcomes achieved and learning so far, what can you say about your interventions and strategies? What worked? Why? Is there a need for adjustment? 7. Annual reflection and Planning Who should take part in the annual planning and reflection?

Implementing Adaptive Approaches in Real World Scenarios: A Nigeria Case Study, with Lessons for Theory and Practice - Bridges, Kate; Woolcock, Michael (The World Bank, 2019)
How does adaptive implementation work in practice? Drawing on extensive interviews and observations, this paper contrasts the ways in which an adaptive component of a major health care project was implemented in three program and three matched comparison states in Nigeria. The paper examines the bases on which claims and counterclaims about the effectiveness of these approaches were made by different actors, concluding that resolution requires any such claims to be grounded in a fit-for-purpose theory of change and evaluation strategy. The principles of adaptive development may be gaining broad acceptance, but a complex array of skills, expectations, political support, empirical measures, and administrative structures needs to be deftly integrated if demonstrably positive operational results are to be obtained, especially when undertaken within institutional systems, administrative logics, and political imperatives that are predisposed to serve rather different purposes.

SAVI Approach Paper 12: Managing Programme Finances to Support Adaptive, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governance in ways that are effective in influencing reform, and that are able to take on a life of their own without continuing donor support. SAVI is also an adaptive programme, putting learning and adaptation at the centre of all decision-making. Money is used and...

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Built to improve: Leveraging realtime M&E for adaptive youth employment programming - Skelton, John (Prospects practice paper, 2, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

SAVI Approach Paper 14: Learning, Adaptation and Communications - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme, aiming to put learning and adaptation at the centre of all decision-making. Learning and adaptation takes place in SAVI at three levels: the work of partners; the work of SAVI delivery teams; and the enabling environment of the programme as a whole. Achieving...

SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Programme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Nigeria Public Sector Accountability and Governance Programme - Business Case - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

SAVI Approach Paper 5: Defining and Measuring Results - SAVI (DFID, 2015)
SAVI aims to facilitate replicable and sustainable processes of citizen engagement in governance. The programme in each state is locally defined, flexible and adaptive, and results are not predictable in advance. Standardised monitoring tools are not applicable, and consequently we have evolved our tools and frameworks during the programme through processes of learning by doing....

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (Synthesis Paper 3, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
 More examples are needed of aid programming that works by being responsive to country realities: politically smart, problem-driven and locally led  DFID’s SAVI programme has revealed a hitherto untapped potential for change leading to better development results at state level in Nigeria  SAVI provides low-profile support to state-level organisations and partnerships, building their capacity to engage constructively with government  It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’  This illustrates the power of facilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance  The set-up of the DFID suite of state-level programmes, with separately managed sector support and ‘governance’ initiatives, has limited realisation of the potential  Key enabling conditions were that DFID provided space for an experience-based design process and permitted tangible results to be judged retrospectively, not pre-programmed

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (IDS Policy Briefing, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.

Enabling citizen-driven improvement of public services. Leveraging Technology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank and Reboot, 2015)
Effective public service delivery begins with knowing whether the services offered are working as intended. We launched a system to enable citizen input on the delivery of public services.

SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of citizens. More responsive, inclusive and accountable attitudes and behaviour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and replicate and sustain reforms beyond the lifetime...

SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated partnership approach, in contrast to the usual approach of grants to civil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-grown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...

SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and partners use to plan and to monitor change – as well as to reflect on and enhance their own effectiveness. It sets out broad stages of attitude and behaviour change over time to facilitate effective citizen engagement in governance processes, systems and structures....

SAVI Approach Paper 6: Engaging Civil Society - SAVI (DFID, 2015)
SAVI state teams provide support to CS groups to become more effective agents of citizens’ voice and public accountability, through a variety of mutually reinforcing interventions. These include: hands-on support to demonstration civil society Advocacy Partnerships (APs) facilitating working partnerships between civil society APs, SHoAs, and the media brokering working relationships between all of these...

SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we also support partners to focus on some issues and form some partnerships and networks which...

SAVI Approach Paper 8: Engaging the Media - SAVI (DFID, 2015)
The overall aim of SAVI engagement with the media is for media representation of citizens’ interests to become normal, and play its part in helping state governments to be more responsive, inclusive and accountable to their citizens. Media partners – individual media personnel and selected media houses – are supported to be more effective agents...

SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting reforms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nigerian state governments and their citizens. SHoAs are supported to be more effective agents of citizen voice and public accountability, demanding better performance from...

SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – but we work in close conjunction with sister programmes who are supporting state governments on governance and sector reforms. SAVI supports non-government and SHoA partners to play their part in promoting more responsive, inclusive and accountable state governance delivering better services for citizens....

‘We have the solutions to our own problems’: supporting civil society in Nigeria - Overseas Development Institute (ODI, 2014)
Development assistance programmes that start from careful analysis of what works and what does not in country contexts are still remarkably rare. One reason for this is the lack of well documented examples of ‘politically’ smart aid programming. To this end, this film outlines the experience of the State Accountability and Voice Initiative (SAVI), a DFID-funded programme in Nigeria providing support to civil society, media and governmental organisations.

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact.  SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

State Accountability and Voice Initiative (SAVI) - Approach Paper Series - SAVI (DFID, 2016)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact. Our approach is summarized in the Introduction to SAVI’s way of working. We have broken our approach down into key components – depicted in the form of our ‘knowledge tree’ –...
Keywords: IMPORTANT

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...

Strengthening Advocacy and Civic Engagemetn in Nigeria - Chemonics (Chemonics International, 2018)

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (Working Paper 525, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

Lessons learned from PERL and partners' response to the COVID-19 crisis - Sharp, Samuel; Nwachukwu, Tochukwu; Srivatsa, Sripriya Iyengar (PERL Programme, 2021)
The first case of COVID-19 in Nigeria was confirmed on 27 February 2020, with the first lockdown orders issued on 30 March 2020. The pandemic and resultant containment measures have had farreaching socio-cultural, economic, financial and political implications, globally as well as in Nigeria. For the Partnership to Engage, Reform and Learn (PERL) and its partners, the pandemic has required considerable adaptation of their strategic approach and working practices. This report reflects on how COVID-19 changed the operating context for PERL’s partners, how PERL responded and what lessons have been learned across delivery teams. For government partners, the most substantial impacts have been to budgets, struck by falling oil prices and reduced economic activity. Universally, states have had to adjust budgets and reforecast, revising budgets downwards and shifting the focus of expenditure towards healthcare. The World Bank’s State Fiscal Transparency, Accountability and Sustainability (SFTAS) Programme has generated powerful incentives for this budget revision, which PERL has been able to work alongside. A range of new governance structures – such as public response committees and task forces – have been established to deal with various aspects of COVID-19 policy, and PERL has had to grapple to maintain its ongoing engagement with these. For civil society organisations (CSOs), the closure of offices from 30 March 2020 has changed the nature of engagement with government. CSOs often developed innovative approaches to maintaining access, including use of social media and direct calls. But the shift to virtual working has been challenging for many CSOs, both in terms of covering the costs of data for virtual meetings and the risks of disengagement and marginalisation for some organisations. In response to this changed context, from March 2020 PERL began to restrategise. The flexible nature of the programme’s workplans, progress markers and budgets enabled activities to be adjusted in a relatively timely manner, with a new workplan approved by the end of April 2020. Central PERL management developed a COVID-19 response strategy which provided a broad framework for adaptations, but allowed substantial autonomy to state and regional teams to lead on reprioritisation according to their understanding of the local context. This was valued by both management and delivery staff. Challenges manifested themselves more in effectively delivering on these adapted workplans than in the process of restrategising – due to two rounds of budget cuts, the merger of DFID and the FCO to form the Foreign, Commonwealth and Development Office (FCDO) and the difficulties of engaging partners virtually. Overall, the pandemic undoubtedly delayed activities (by roughly three months for deprioritised areas of work), but resulted in an array of new, tailored interventions under its broad categories of work. Interventions relating to the health sector became more prevalent, as did work supporting budget adjustments. Domestic resource mobilisation and education interventions were often adjusted to be more relevant to the COVID context or experienced delay. The report provides short illustrative case studies of PERL’s adaptations to: support budget revisions; work with media partners on COVID-19 sensitisation; tracking and advocacy for palliative distribution; and support for the introduction of tax relief. There is some evidence, albeit partial, that PERL was able to take advantage of windows of opportunity offered by the pandemic to drive ahead with certain ongoing reform initiatives.

Pushing boundaries: Advocacy evaluation and real-time learning in an HIV prevention research advocacy coalition in sub-Saharan Africa - Dasmariñas, Jules; Schlangen, Rhonda (New Directions for Evaluation, 2021)
Evaluation processes that facilitate learning among advocates must be nimble, creative, and meaningful while transcending putative performance and accountability management. This article describes the experience, lessons, and trajectory of one such approach, Simple, Participatory Assessment of Real Change (SPARC), that a transnational HIV prevention research advocacy coalition pilot-tested in sub-Saharan Africa. Inspired by the pioneering work of the outcome harvesting (OH) and participatory evaluation community, we recuperate advocates' centrality as storytellers, sense-makers, and strategists in advocacy evaluation and describe how we recalibrated SPARC to meet their evaluation and learning needs. This article highlights the normative value of deliberative discourse in evaluation as it contributes to the interpretation of OH and the enrichment of the theory and practice of advocacy evaluation.

SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...

A Guide to Participatory Outcome-Focused Monitoring with Most Significant Change, Outcome Harvesting, and Outcome Mapping - Smith, Richard (CARE, 2023)
Audience This guidance is primarily aimed at development and humanitarian professionals who design or manage monitoring and evaluation processes to support design and implementation of qualitative monitoring using Most Significant Change (MSC), Outcome Harvesting (OH), or Outcome Mapping (OM), which are participatory, outcome-focused qualitative methods. Purpose This guidance is a resource to strengthen qualitative monitoring, specifically addressing commonplace gaps or weakness in the monitoring of complex development and humanitarian projects. Importantly, these gaps include: 1. Lack of evidence about unexpected, as well as expected, changes or outcomes, especially during project implementation. 2. Limited documentation about whether and how a project contributed to change. Such information is vital to learning about what worked and how to build on successes. 3. Limited data to inform the review of theories of change, which limits their function and relevance. Addressing these monitoring gaps has the potential to contribute to more informed and effective adaptive management and learning. This guidance can be used to support the design and implementation of monitoring exercises using MSC, OH, and OM. Specifically, it supports users in choosing among MSC, OH, and OM or blending elements from these approaches. Additionally, it provides practical tips and examples - including expertise gained during the two pilot qualitative monitoring activities conducted in Niger and Bangladesh - as well as other publicly available materials. 1. Relevant CARE guidance and tools include: 1. Qualitative Methods Guidance Note for Monitoring, Evaluation and Learning (MEL) at CARE; 2. Outcome Mapping Manual: Development of a monitoring system for the Right to Food project using Outcome Mapping, CARE Nepal; 3. Tipping Point MEL Methods Brief: Outcome Mapping; 4. The Rolling Profile Tool.

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice